Vitamin D deficiency and reduced bone mineral density in multiple sclerosis: effect of ambulatory status and functional capacity - Ozgocmen, S; Bulut, S; Ilhan, N; Gulkesen, A; Ardicoglu, O; Özkan, Y (Springer Japan Kk, 2005)
Multiple sclerosis ( MS) is a chronic disease and a major cause of disability in young adults. The aims of this study were to assess bone mass in patients with MS in comparison to healthy age- and sex-matched controls, and to evaluate factors influencing bone mineral density (BMD), and the relationship of the pain threshold at peripheral and axial sites with BMD in MS. Thirty-one patients with MS and 30 matched healthy controls participated in the study. The Kurtzke expanded disability status scale (EDSS) and the functional independence measure (FIM) were used to scale disability, mobility, and functional status. Serum 25( OH) vitamin D levels were measured. BMD was measured using dual X-ray absorptiometry (DXA). MS patients had significantly lower BMD at the lumbar spine (L2-L4) and femur trochanter compared to the matched controls. BMD of the lumbar spine was nearly 1 SD lower in MS patients compared with the healthy reference population (Z scores). MS patients had significantly lower vitamin D levels (17.3 ng/ml vs 43.1 ng/ml; P < 0.001) compared to controls, and 19 patients (61%) had a serum level of vitamin D that was less than 20 ng/ml. EDSS scores in the patients were inversely correlated with proximal femur BMD but not with spinal BMD. There was a negative correlation with the cumulative steroid dose and BMD only for femur trochanter BMD. Total myalgia scores for paravertebral muscles correlated significantly with spinal BMD. In conclusion, BMD is significantly lower in MS patients than in healthy controls, vitamin D deficiency is prevalent in MS, and ambulatory status is a determinative factor for osteoporosis in MS. Patients should be encouraged to have adequate sunlight exposure and to increase their mobility. Specific strengthening exercises for hip and back muscles in MS patients would have a substantial impact on bone density, osteoporosis, fracture risk, and mobility.
Keywords: multiple sclerosis; osteoporosis; ambulation; vitamin D